2007
DOI: 10.1111/j.1439-0418.2006.01140.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐resistance and biochemical mechanisms of abamectin resistance in the B‐type Bemisia tabaci

Abstract: To understand the risk of resistance and the possible mechanisms of resistance to abamectin in B-type Bemisia tabaci (Gennadius) better, a resistant strain of B. tabaci was selected in the laboratory and cross-resistance pattern and resistance mechanisms to abamectin were investigated. The NJ-Abm strain of B. tabaci was derived from a field population (NJ) collected in Nanjing, China in 2002 with 18 generations of selection with abamectin in the laboratory. Compared with the unselected NJ strain, the selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
2
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 40 publications
2
53
2
3
Order By: Relevance
“…This is somewhat consistent with that the major mechanism in all samples investigated so far has appeared to be enhanced detoxification by cytochrome P450 (Rauch & Nauen, 2003). Furthermore, the cytochrome P450 system has been previously reported to be involved in the resistance to many insecticides in many insects, including abamectin resistance in Leptinotarsa decemlineata (Argentine et al, 1992), Tetranychus urticae and B. tabaci (Wang & Wu, 2007), permethrin resistance in Culex quinquefasciatus (Liu et al, 2011;Gong et al, 2013), and imidacloprid resistance in Nilaparvata lugens (Bass et al, 2011). In particular, the resistance of B. tabaci to imidacloprid was strongly related to enhanced detoxification by cytochrome P450 Feng et al, 2010), and cytochrome P450 activity was significantly greater in the resistant strains than in the corresponding susceptible strains (Rauch & Nauen, 2003).…”
Section: Gene Expression Profiles For Coe Gst and Cytochrome P450 Gesupporting
confidence: 74%
See 1 more Smart Citation
“…This is somewhat consistent with that the major mechanism in all samples investigated so far has appeared to be enhanced detoxification by cytochrome P450 (Rauch & Nauen, 2003). Furthermore, the cytochrome P450 system has been previously reported to be involved in the resistance to many insecticides in many insects, including abamectin resistance in Leptinotarsa decemlineata (Argentine et al, 1992), Tetranychus urticae and B. tabaci (Wang & Wu, 2007), permethrin resistance in Culex quinquefasciatus (Liu et al, 2011;Gong et al, 2013), and imidacloprid resistance in Nilaparvata lugens (Bass et al, 2011). In particular, the resistance of B. tabaci to imidacloprid was strongly related to enhanced detoxification by cytochrome P450 Feng et al, 2010), and cytochrome P450 activity was significantly greater in the resistant strains than in the corresponding susceptible strains (Rauch & Nauen, 2003).…”
Section: Gene Expression Profiles For Coe Gst and Cytochrome P450 Gesupporting
confidence: 74%
“…It has been reported that the enhanced metabolism mediated by cytochrome P450 monooxygenase (P450) and glutathione S-transferase (GST) was reported to be involved in abamectin resistance (Wang & Wu, 2007). The resistance to neonicotinoid and thiamethoxam is mediated in part by cytochrome P450 Rauch & Nauen, 2003;Feng et al, 2009Feng et al, , 2010 In B. tabaci, a specific cytochrome P450, CYP6CM1 was involved in the resistance to imidacloprid and could metabolize this insecticide in vitro (Karunker et al, 2008(Karunker et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature there are contradictory results between GST-CDNB activity levels and abamectin resistance. For example, while increased GST-CDNB activities were determined in abamectin resistant Tetranychus urticae and Bemisia tabaci [38,39], GST-CDNB activity was not changed in abamectin resistant T. absoluta in Brazil [18]. Furthermore, it should be also considered that GST activity levels depend on metabolic rate of animals, increased respiration of mitochondria leads to accumulation of reactive oxygen species [40].…”
Section: Discussionmentioning
confidence: 99%
“…The level of ethion resistance detected in the populations from Al-Ahsa and AlQatif suggest that the establishment of ethion resistance in the RPW populations is in its initial stages. The role of GST in resistance to synthetic insecticides has been previously evidenced in many pests, including Aedes aegypti (Lumjuan et al, 2005), Anopheles gambiae (Ortelli et al, 2003), Bemisia tabaci (Wang and Wu, 2007), L. decemlineata (Argentine et al, 1992), Liriomyza sativae (Wei et al, 2014), Musca domestica and Tetranychus urticae (Kim et al, 2004).…”
Section: Discussionmentioning
confidence: 99%